THE EFFECT OF DISTRIBUTIVE JUSTICE AND MOTIVATION INTRINSIC TO JOB SATISFACTION AND EMPLOYEE PERFORMANCE IN MSMEs IN THE CULINARY SECTOR IN THE SPECIAL REGION OF YOGYAKARTA - Gigih Tegar Tyofyan; Heru Kurnianto Tjahjono; Susanto Susanto (International Journal Labs, 2022)
Introduction: This study aims to determine the effect of distributive justice and intrinsic motivation on job satisfaction and performance Methods: This research is quantitative research, the method uses the SEM method, and uses the IBM SPSS AMOS analysis tool. The sample in this study amounted to 140 employees of SMEs in the culinary field at D.I. Yogyakarta Results: The results showed that Distributive Justice and Intrinsic Motivation had a positive effect on performance either directly or through the mediation of job satisfaction variables. Conclusion and suggestion: With a high level of distributive justice and intrinsic motivation, it will improve the performance of MSME employees. However, the effect of distributive justice and intrinsic motivation on performance will be higher through job satisfaction variables